2022
DOI: 10.1021/acs.jcim.2c00562
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Adsorption of SARS-CoV-2 Spike Protein on Polystyrene Surface

Abstract: A prominent feature of coronaviruses is the presence of a large glycoprotein spike (S) protruding from the viral particle. The specific interactions of a material with S determine key aspects such as its possible role for indirect transmission or its suitability as a virucidal material. Here, we consider all-atom molecular dynamics simulations of the interaction between a polymer surface (polystyrene) and S in its up and down conformations. Polystyrene is a commonly used plastic found in electronics, toys, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…In another MD study [109] it was also found that the RBD region of spike displays a RMSD of 0.5 nm. In another MD study by Sahihi and Faraudo [110] , the average RMSD values without glycans of S protein were found to be about 4.96 ± 0.19 Å for down conformations (corresponds to our S-without-GlcNAc system)”. Both of our systems reach stability after the first 20 ns of the simulation ( Figure 4 a).…”
Section: Resultsmentioning
confidence: 74%
“…In another MD study [109] it was also found that the RBD region of spike displays a RMSD of 0.5 nm. In another MD study by Sahihi and Faraudo [110] , the average RMSD values without glycans of S protein were found to be about 4.96 ± 0.19 Å for down conformations (corresponds to our S-without-GlcNAc system)”. Both of our systems reach stability after the first 20 ns of the simulation ( Figure 4 a).…”
Section: Resultsmentioning
confidence: 74%
“…Our MD simulations indicate that the virus spikes can be attached to sebaceous human skin without any deformation or alteration and retain their hydration 10 . Also, our simulations indicate that they can remain adsorbed with a high affinity over common plastics without any substantial deformation 11 . Only some materials such as metals 12 or carbon based materials 13 seem to be able to have a substantial impact on the adsorbed virus spikes.…”
Section: Introductionmentioning
confidence: 68%
“…The force-field employed in the simulations was CHARMM36 33,34 as in 31 and as in our previous simulations of the SARS-CoV-2 Spike glycoprotein 10,11,13 . The force field also includes an appropiate parametrization for the surfactants.…”
Section: B All Atomic (Aa) Simulationsmentioning
confidence: 99%
“…On the other hand, Faraudo et al investigated the spike protein interactions with the surfaces of different materials including cellulose, graphite, and polystyrene. Their obtained results indicated that the properties of the surfaces can affect the dynamical features of the spike protein. Moreover, in the structure of the spike protein, the RBD part plays a more important role in the corresponding interactions with the surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…To have a comprehensive insight into the dynamical behavior of the RBD on the surface of different materials, the obtained results were compared with the previous studies. 19 , 38 , 39 , 73 75 In the previous study, we also compared the RBD interactions with the graphene and phosphorene nanosheet. 19 Our obtained results indicated that the phosphorene nanosheet can be a better candidate for coronavirus detection than the graphene nanostructure.…”
Section: Resultsmentioning
confidence: 99%